2019
DOI: 10.1002/cbin.11242
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas‐mediated Fubp1 silencing disrupts circadian oscillation of Per1 protein via downregulating Syncrip expression

Abstract: Most living organisms have physiological and behavioral circadian rhythms controlled by molecular clocks. In mammals, several core clock genes show self‐perpetuating oscillation profiles of their messenger RNAs (mRNAs) and proteins through an auto‐regulatory transcription–translation feedback loop (TTFL). As a critical component in the molecular clock system, Period 1 (Per1) contributes to the maintenance of circadian rhythm duration predominantly in peripheral clocks. Alterations in Per1 expression and oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When it is abnormal, the resulting changes to the normal rhythm of cell proliferation lead to the occurrence of tumors. PER1 has a role in feeding and active behavior in mammals and is controlled by circadian rhythms (Kim et al, 2020). From a non-tumor perspective, PER1 is related to conditions such as Parkinson's disease, obesity, sleep, drug resistance, and premature ovarian insufficiency (Zheng et al, 2019;Delgado-Lara et al, 2020;EmeklI et al, 2020;Mabrouk et al, 2020;Arellanes-Licea et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When it is abnormal, the resulting changes to the normal rhythm of cell proliferation lead to the occurrence of tumors. PER1 has a role in feeding and active behavior in mammals and is controlled by circadian rhythms (Kim et al, 2020). From a non-tumor perspective, PER1 is related to conditions such as Parkinson's disease, obesity, sleep, drug resistance, and premature ovarian insufficiency (Zheng et al, 2019;Delgado-Lara et al, 2020;EmeklI et al, 2020;Mabrouk et al, 2020;Arellanes-Licea et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that, based on utilizing the publicly available gene expression data set and ChIP results, the transcription factor Fubp1 can bind to the promoter region of SYNCRIP and promote its transcription. 43 Furthermore, it was reported that Fubp1 can form an RNA-protein complex with lncRNA. 44 Accordingly, we speculated that lncNT5E might recruit Fubp1 to regulate SYNCRIP expression.…”
Section: Discussionmentioning
confidence: 99%
“…There were few literature regarding transcription factors or regulatory complexes related to SYNCRIP. A recent study reported that, based on utilizing the publicly available gene expression data set and ChIP results, the transcription factor Fubp1 can bind to the promoter region of SYNCRIP and promote its transcription 43 . Furthermore, it was reported that Fubp1 can form an RNA‐protein complex with lncRNA 44 .…”
Section: Discussionmentioning
confidence: 99%